Serotonergic mechanisms enhance platelet-mediated thrombogenicity - Galan, Ana M.; Lopez-Vilchez, Irene; Diaz-Ricart, Maribel; Navalon, Fulgencio; Gomez, Esther; Gasto, Cristobal; Escolar, Gines (Thrombosis and Haemostasis, 2009)
Although it is generally acknowledged that serotonin (5-HT) is a weak agonist for human platelets, recent information suggests an association between serotonergic mechanisms and cardiovascular risk. We investigated the action of 5-HT on adhesive, cohesive and procoagulant properties of human platelets. Impact of 5-HT on whole blood coagulation and thrombin generation was measured by modified thromboelastometry (TEM) and specific fluorogenic assays. We evaluated the effects of 5-HT on thrombus formation in an in-vitro model of thrombosis using human flowing blood. In platelet-rich plasma (PRP), 5-HT favoured the expression of CD62-P, and procoagulant molecules on platelet membranes. These effects were potentiated in the presence of Ca++ and/or ADP. Incubation with 5-HT accelerated clotting times and augmented clot strength in whole blood TEM, and enhanced thrombin generation in PRP. In perfusion studies, 5-HT significantly increased fibrin deposition at low shear (300s-1) and enhanced platelet thrombus formation on the damaged vascular surface at high shear (1,200s-1). Selective inhibition of serotonin reuptake (SSRI) attenuated effects of 5-HT on platelet activation and downregulated the prothrombotic tendencies observed in the previous experimental conditions. In general, reductions of thrombogenic patterns observed with SSRI were more evident under shear conditions (aggregation and perfusion systems) and less evident under steady conditions (TEM and thrombin generation assays). In conclusion, 5-HT is not a weak agonist for human platelets; instead it accentuates platelet activation, potentiates procoagulant responses on human blood and increases thrombogenesis on damaged vascular surfaces. The remarkable antithrombotic actions achieved through SSRI deserve further mechanistic and clinical investigations.
Keywords: Platelet physiology; platelet pharmacology; serotonin; thrombogenesis